THE CONCEPT OF MEANING IN THE CONTEXT OF THE STUDENT-CENTERED EDUCATION - Svetlana V. Volkova (Высшее образование в России)
The article is devoted to the understanding and elaboration of the philosophyand methodology of humanities. Based on the philosophy of education, the author discloses some characteristics, which belong to the human intellectual processes and processes of transmission of knowledge in particular. The author proposes the concept of meaning as a person’s «functional organ», and considers its connection to the conception of the student% centered education.